2009
DOI: 10.1021/la900283t
|View full text |Cite
|
Sign up to set email alerts
|

Heats of Adsorption for Seven Gases in Three Metal−Organic Frameworks: Systematic Comparison of Experiment and Simulation

Abstract: The heat of adsorption is an important parameter for gas separation and storage applications in porous materials such as metal-organic frameworks (MOFs). There are, however, few systematic studies available in the MOF literature. Many papers report results for only one MOF and often only for a single gas. In this work, systematic experimental measurements by TAP-2 are reported for the heats of adsorption of seven gases in three MOFs. The gases are Kr, Xe, N2, CO2, CH4, n-C4H10, and i-C4H10. The MOFs studied ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
175
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(196 citation statements)
references
References 39 publications
18
175
1
1
Order By: Relevance
“…[54][55][56] The isosteric heat for CO 2 is around 17.7 kJ mol À1 and does not vary with the amount of CO 2 adsorbed (10 and 30 cm 3 g À1 ). In the case of CH 4 (4 and 10 cm 3 g À1 ), the isosteric heat is around 14.4 kJ mol…”
Section: Gas Adsorption Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…[54][55][56] The isosteric heat for CO 2 is around 17.7 kJ mol À1 and does not vary with the amount of CO 2 adsorbed (10 and 30 cm 3 g À1 ). In the case of CH 4 (4 and 10 cm 3 g À1 ), the isosteric heat is around 14.4 kJ mol…”
Section: Gas Adsorption Resultsmentioning
confidence: 98%
“…The most plausible explanation is that the CO 2 adsorption enthalpy is significantly smaller than that of CH 4 . [54][55][56] Besides, the adsorption ability of CO 2 was hardly influenced by CH 4 , which can be deduced from the similar relative band areas in the final plateau regions. In contrast, the CH 4 adsorption is strongly disturbed in the presence of CO 2 , which is indicated by the lower value of the IR bands of CH 4 in the region of 3024-3008 cm À1 (Supporting Information, Figure S4).…”
mentioning
confidence: 81%
“…MOFs have several advantages as compared to zeolites: cheaper and simpler synthesis, high diversity of pore structures, and numerous possibilities for postsynthetic modifications. Despite the importance of MOFs for noble gas storage and separation, only a few studies of krypton and xenon adsorption are reported to date [1][2][3][4][5][6][7][8][9][10][11][12] and only three studies of adsorption sites of noble gases in MOFs by means of X-ray or neutron diffraction, [13][14][15] despite the fact that the major adsorption sites and their binding energies are the key features of a material that determines its adsorption properties at a given temperature and pressure, and their identification is a basis for further modifications of the crystal structure of the MOF in order to achieve maximal storage capacity and selectivity. The study of noble gas adsorption in HKUST-1 15 revealed that the interaction of noble gases with MOFs can be completely different from the adsorption of other atoms and molecules like D 2 , C 2 H 2 , CO 2 , or CH 4 (methane is a nonpolar gas whose diameter and polarizability are similar to those of Kr).…”
Section: Introductionmentioning
confidence: 99%
“…There are a small number of counterexamples to this general phenomenon where the heat of adsorption varies non-monotonically [55] or even smoothly increases [58] as a function of loading. Snurr et al [66] used simulations to calculate the initial heat of adsorption for HKUST-1 and found a negative dependence of this quantity on temperature. They argued that in this case the binding site that dominates the initial adsorption of CO 2 changes as a function of temperature because of an interplay between enthalpic and entropic effects.…”
mentioning
confidence: 99%